2013
DOI: 10.1016/j.jadohealth.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Pelvic Inflammatory Disease Among Adolescents in the Emergency Department

Abstract: Objective In 2002 the CDC broadened the pelvic inflammatory disease (PID) diagnostic criteria to increase detection and prevent serious sequelae of untreated PID. The impact of this change on PID detection is unknown. Our objective was to estimate trends in PID diagnosis among adolescent emergency department (ED) patients before and after the revised CDC definition and identify factors associated with PID diagnoses. Methods We performed a retrospective repeated cross-sectional study using the National Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
0
23
2
1
Order By: Relevance
“…This is the first Australian study to assess PID rates using routinely collected ED data. Our findings of increasing PID rates contrast with a study in the USA that found falling PID rates (2002–2009) among adolescents attending EDs 14. For EP, stable or declining admission rates using live birth denominators have been reported in Australia and internationally until the 2000s, with increases in some groups 7 8 21.…”
Section: Discussioncontrasting
confidence: 90%
“…This is the first Australian study to assess PID rates using routinely collected ED data. Our findings of increasing PID rates contrast with a study in the USA that found falling PID rates (2002–2009) among adolescents attending EDs 14. For EP, stable or declining admission rates using live birth denominators have been reported in Australia and internationally until the 2000s, with increases in some groups 7 8 21.…”
Section: Discussioncontrasting
confidence: 90%
“…Some studies found that Black women were more affected by acute PID. 16,18 The majority of patients in our series had secondary school education (54.3%). This can be explained by the fact that students were more represented.…”
Section: Resultsmentioning
confidence: 69%
“…350-356) published in this issue of Current Opinion in Obstetrics and Gynecology, she provides an 'alternative look' at the published data on adolescents with PID, and concludes that there is limited evidence to guide the best practice strategies for young and middle adolescents with PID. The evidence supports the fact that adolescents and adult women receive suboptimal treatment for PID; large database reviews demonstrate that only 30-40% of patients received care according to the U.S. Centers for Disease Control (CDC) treatment guidelines [5,6]. Because adolescents are at increased risk for poor adherence to treatment regimens, and at increased risk of sexually transmitted disease (STD) reacquisition, they risk adverse reproductive health outcomes including infertility, recurrent PID, and chronic pelvic pain.…”
Section: This Section Of Current Opinion In Obstetrics Andmentioning
confidence: 80%